Angel, seed and founders influence on fintech funding: an emerging market context - Giaquinto, Luisa Herck (2019)
This study examines the difference between FinTechs that received private equity and venture capital finance with those that did not receive. We test this with a sample of 2,524 companies across 76 countries over 2008-2018. We find that country-specific determinants of start-up funding are also relevant to FinTechs. Furthermore, companies in financing and payments categories are more likely to receive funding. We show a positive relationship between having received an angel and a seed round with follow-on finance, and a negative relationship with having a single founder. The impact of the seed finance and the single founder is weaker in an emerging market.